Workload Control Order Release With Controllable Processing Time Policies: An Assessment by Simulation - Renna, Paolo (International Journal of Industrial Engineering and Management, 2022)
Workload Control is used in manufacturing systems to obtain more predictable throughput times and accurate delivery dates. The models proposed in the literature are typically focused on machines with fixed processing time. This study, therefore, uses simulation to investigate the performance of the Workload Control method with a controllable processing time of the machines. This research proposes four models to support the decisions on the time to reconfigure the machines and the number of machines reconfigured. The time decision follows two strategies as periodic and continuous, while the machines reconfigured can be all or two considering the workload. The combinations of these strategies lead to four models that are tested in different conditions of reconfiguration times and the number of bottlenecks. The results suggest as the proposed models allow to improve delivery time performance and a more uniform distribution of workload among the machines of the manufacturing systems. Article history: Received (January 20, 2022); Revised (July 15, 2022); Accepted (July 20, 2022); Published online (July 27, 2022)